2005
DOI: 10.1002/anie.200462205
|View full text |Cite
|
Sign up to set email alerts
|

A Rock‐Salt‐Like Lattice Structure Consisting of Monocationic and Monoanionic AuIAgICuII Supramolecular Cages of D‐Penicillaminate

Abstract: Over the past decade, considerable interest has been devoted to the controlled synthesis of metallosupramolecular species, such as finite coordination rings and cages and infinite coordination polymers, not only because of their intriguing structural diversity but also because of their potential as new functional materials.[1] While the most common approach to obtain metallosupramolecules is based on the self-assembly of multidentate organic ligands and metal ions, our synthetic strategy has been directed towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The reactiono f83 with CuCl 2 followed by crystallization gave rise to as alt containing the three coinage metal atoms, which is composed of large monocationic and monoanionic cages containing 20 and 21 metal atoms, respectively.T hese cages are arranged in as upramolecular ionic structure resembling that of the rock salt. [72] Te tranuclear complexes containing two square-planar centers have been isolated by reactiono fH 2 [80]w ith Ni II , [73] Pd II [74] or Pt II [74] salts (Figure 25). The cis,cis or trans,trans forms of these complexes (84 and 85)h ave been isolated as potassium salts.…”
Section: Metalloligands Containing Amino Acid Binding Sitesmentioning
confidence: 99%
“…The reactiono f83 with CuCl 2 followed by crystallization gave rise to as alt containing the three coinage metal atoms, which is composed of large monocationic and monoanionic cages containing 20 and 21 metal atoms, respectively.T hese cages are arranged in as upramolecular ionic structure resembling that of the rock salt. [72] Te tranuclear complexes containing two square-planar centers have been isolated by reactiono fH 2 [80]w ith Ni II , [73] Pd II [74] or Pt II [74] salts (Figure 25). The cis,cis or trans,trans forms of these complexes (84 and 85)h ave been isolated as potassium salts.…”
Section: Metalloligands Containing Amino Acid Binding Sitesmentioning
confidence: 99%
“…While studying the reactivity of the 3-mercapto derivative of valine (d-penicillamine or d-H 2 pen) bound to a gold(I) centre towards various metal ions (Toyota et al, 2005;Taguchi et al, 2007), we found that red crystals containing Au I and Ni II atoms in a 2:1 ratio are formed when a solution containing [Au(d-pen) 2 ] 3and Ni 2+ was allowed to stand in a refrigerator for two months. We report herein the crystal structure of (I) containing a d-carbaminopenicillaminate (d-cp) ligand that bridges two Au I atoms through a thiolate group.…”
Section: Commentmentioning
confidence: 99%
“…Finally, the affinity of coinage metals for sulfur ligands was recently used to create a unique metallosupramolecular architecture containing Au(I), Ag(I) and Cu(II) in the same metal frameworks [628]. Thus, the reaction of (NH 4 )[Au(D-Hpen) 2 ] with AgNO 3 (1 : 1 molar ratio), followed by treatment with excess of CuCl 2 , afforded the isolation of blue crystals of a heterometallic aggregate with a rock-salt-like lattice structure.…”
Section: Gold-silver Compoundsmentioning
confidence: 99%